The Use of Non-audit Services of Thai Listed Companies - Baotham, Sumintorn (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This research aims to study the volume and types of non-audit services used by the Thai listed companies. The sample of this research was the companies listed on the Stock Exchange of Thailand with non-audit services. In addition, they should disclose the non-audit services from 2013 to 2015. The tool used for collecting data is a self-checklist survey summary which is created by the researcher. The information is disclosed in the annual reports and Annual Registration Statements (Form 56-1) for the years 2013-2015. The study indicated that 31% or 120 companies from 388 companies disclose the non-audit services. The groups with the most non-audit services were Real estate and construction, Industrial and Financial Groups. It also found that non-audit fees for each company were not disclosed in the same format. Information from this research is recommended to the regulatory authorities. Listed companies should disclose their non-audit fees in the same pattern in order that the data can be compared and analyzed in depth. The information should also be provided to the Audit Committee for consideration of the appropriateness and impact of the auditor’s performance